The role of immunity in comorbid pain and depression - Antonella Ciaramella; Giancarlo Carl (Exploration of Immunology)
The narrative review aims to shed light on the influence of inflammation in the comorbid chronic pain and major depressive disorder (MDD). This connection is known to be multifactorial, with a dynamic interaction between genetic and epigenetic factors. However, a growing body of evidence has shown that the co-presence of MDD and pain is underlain by immune mechanisms involved in the persistence of the inflammatory process. In particular, the cytokines released following activation of the innate immune system during inflammation cause changes at the endocrine level that result in glucocorticoid resistance, as well as altering the synthesis and metabolism of some central nervous system (CNS) mediators. Cytokines appear to generate neuroinflammation by activating normally protective microglia. Various other mechanisms, including changes in the function of the glutamatergic, GABAergic, and serotonergic systems are also implicated, but inflammation-induced reduction of BDNF (brain-derived neurotrophic factor) appears to be the deciding factor. In turn, neuroinflammation leads to sickness behavior, which is characterized by anhedonia and social withdrawal. This review explored these mechanisms, which may be at the root of comorbid pain and MDD. Although intriguing, however, most available evidence comes from animal studies, and rigorous clinical exploration is warranted.